A constructive method and a guided hybrid GRASP for the capacitated multi-source Weber problem in the presence of fixed cost - Luis, Martino; Salhi, Said; Nagy, Gabor (SAGE Publications, 2015)
This paper presents a new variant of the capacitated multi-source Weber problem that introduces fixed costs for opening facilities. Three types of fixed costs are considered and experimented upon.A guided constructive heuristic scheme based on the concept of restricted regions and a greedy randomized adaptive search procedure (GRASP) are proposed.The four known data sets in the literature, typically used for the uncapacitated multi-source Weber problem, are adapted by adding capacities and facility fixed costs and used as a platform to assess the performance of our proposed approaches.Computational results are provided and some research avenues highlighted.